Synthesis and Characterization of Poly(o-methoxyaniline) - Sankar, A.; Ragunathan, V.; Mohankumar, K. (Asian Journal of Chemistry, 2011)
Poly(o-methoxyaniline) was prepared chemically from the monomer o-methoxyaniline using 2-chloroethylphosphonic acid. It was characterized by UV-visible, IR and TGA methods. The solubility tests were performed at room temperature for the doped and dedoped polymers in different solvents. The conduction of the polymer samples were determined at room temperature. The morphology of the polymer samples was studied by scanning electron microscopy.